2021
DOI: 10.46291/ispecjasvol5iss2pp439-455
|View full text |Cite
|
Sign up to set email alerts
|

Organik ve Konvansiyonel Koşullarında Bazı Makarnalık Buğday (Triticum durum L.) Genotiplerinin Performanslarının Değerlendirilmesi

Abstract: Organik koşullar altında yüksek tane verimi elde etmenin önündeki en büyük engel besin element yetersizliği ve yabancı ot yoğunluğudur. Buğdayda uzun bitki boyuna, erken çiçeklenmeye ve olgunlaşmaya sahip bitkilerin yabancı otlar ile daha iyi rekabet edebileceği ve organik koşullarda daha iyi verim verebileceği öngörülmektedir. Çalışma, 2019-2020 bitki yetiştirme sezonunda Dicle Üniversitesi Ziraat Fakültesi Tarla Bitkileri Bölümü Araştırma ve Uygulama Alanı’nda yağışa dayalı koşullarda yürütülmüştür. Yerel çe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In previous studies, Bahar and Bahar (2016) 15.15-26.73 kg ha -1 , Kodaş et al (2015) 19.00-32.90 kg ha -1 , Yıldırım et al (2021) 9.01 -50.96 kg ha -1 , Yorulmaz et al (2022) 8.94 -37.57 kg ha -1 . Özkan and Akıncı (2021) found that the mean grain yield was 34.43 kg ha -1 under organic conditions and 44.99 kg ha -1 under conventional conditions in their study. For example, in this field experiment, the genotypes YE-31 and DZ17-1 showed the highest grain yield in different years.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In previous studies, Bahar and Bahar (2016) 15.15-26.73 kg ha -1 , Kodaş et al (2015) 19.00-32.90 kg ha -1 , Yıldırım et al (2021) 9.01 -50.96 kg ha -1 , Yorulmaz et al (2022) 8.94 -37.57 kg ha -1 . Özkan and Akıncı (2021) found that the mean grain yield was 34.43 kg ha -1 under organic conditions and 44.99 kg ha -1 under conventional conditions in their study. For example, in this field experiment, the genotypes YE-31 and DZ17-1 showed the highest grain yield in different years.…”
Section: Resultsmentioning
confidence: 77%
“…According to Bahar and Bahar (2016), the protein content ranged from 13.00% to 14.70% under organic conditions. Özkan and Akıncı (2021) found that the mean protein content of the genotypes was 12.05% under organic conditions and 12.74% under conventional conditions. These findings suggest that there is considerable variation in protein content among different genotypes and across different years of the study.…”
Section: Resultsmentioning
confidence: 94%